ANALISIS PROSPEK INVESTASI MEDEL BUSINNES PLAN UNTUK PENGEMBANGAN PEMBERDAYAAN BUDIDAYA IKAN NILA DI KECAMATAN TOMBATU KABUPATEN MINAHASA TENGGARA - Efendy Rasjid; Mariska Walean; Meiske Manopo; Jemmry Winokan (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2020)
Many businnes people plan only pursue large profits without making carefull planning in managing financial aspects. To anticipate something that is not wanted in the future, people who want to start a business must make planning in advance in order to minimize the risks tha may occur in the future. That purpose of this research : 1) Identifying the development process of tilapia culvination empowerment, 2) Knowledge and Skills, 3) Equipment and equipment in tilapia culvination, and 4) To know the feasibility of the business by using investment criteria Pay Back Period, Net Present Value and profit analyss method Break Event Point in tilapia cultivation business. The type of research used bay reserachers is a type of mixed methods research, based on the results of NPV analysis shows a positive value or more than 0, this indicates that the tilapia cultivation business is worth running. Furthermore, based on the calculation of Break Event Point shows that tilapia cultivation business in the community in Tombatu District, Southeast Minahasa Regency deserves to be developed an able to increase income and economy of the community.